Culture change in New Zealand rugby - Narasimhan, Varsha; Bridgman, Todd (London : SAGE Publications: SAGE Business Cases Originals, 2020)
This case concerns a high-profile controversy involving a promising New Zealand rugby player who was convicted of assault following a street fight. Sections of the public perceived that the player had been treated leniently by the court and his rugby organisation, so to not compromise his future professional career. The rugby organisation commissioned an independent review of its culture, which recommended a culture change programme. The case highlights the complexity of undertaking culture change in a large organisation that consists of diverse subcultures. It presents a series of first-person perspectives from various stakeholders—a culture expert, the rugby organisation CEO, a member of the panel formulating a new code of conduct, two amateur players, and a sportsperson who has represented New Zealand internationally in another sport. We recommend the case be analysed using Joanne Martin's three perspectives on culture framework.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Rugby football -- New Zealand -- Social aspects -- Case studies; Rugby Union football -- New Zealand; Rugby Union football players -- New Zealand